The relationship between addiction and hikikomori tendencies: a case-control study - Muris, Peter; van de Pasch, Veerle; van Kessel, Janno; Peet, Josine (Frontiers in Psychiatry, 2023)
Aim The present study examined the relationship between addiction and hikikomori (extreme social withdrawal) symptoms. Method A group of clinically referred addiction patients (n = 31) and a group of age- and gender-matched non-clinical controls (n = 34) completed a self-report scale for measuring hikikomori symptoms (the Hikikomori Questionnaire-25) along with some other questionnaires assessing substance use (frequency and severity) and quality of life. Results The results showed that addiction patients displayed significantly higher levels of hikikomori symptoms than the non-clinical control (Cohen's d = 3.41); 87.1% even showed such a high score that they were identified as being at risk for the hikikomori syndrome (vs. only 2.9% in the non-clinical control group). Correlational analyses revealed that within the addiction group, the severity of the substance use problem (as quantified by an index of craving) correlated positively with the level of hikikomori symptoms and negatively with quality of life. In other words, the more severe the addiction, the more extreme the social withdrawal tendencies and the lower the quality of life. Conclusion Altogether, the findings provide further support for the marked social impairments of people with substance use problems and underline that this should be an important target of intervention.